2021
DOI: 10.1016/j.scitotenv.2020.142874
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lockdown on particulate matter concentrations in Colombia during the COVID-19 pandemic

Abstract: The first confirmed case of COVID-19 in Colombia was reported on March 6, 2020. For this reason, on March 25, preventive isolation was declared mandatory. These measures involved the suspension of economic activities and drastically reduced the number of vehicles on the road. The objective of this study is to evaluate the impact of the lockdown due to the COVID-19 pandemic on PM 2.5 concentrations at 5 monitoring stations and aerosol optical depth values of the Terra/MODIS satellite. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
1
20
1
4
Order By: Relevance
“…Focusing on the AOD, a significant reduction (20-60%) was obtained in eastern China, while southeast Asia, eastern US and most European regions experienced a reduction reaching 40% [19,34,35]. However, in areas significantly impacted by seasonal biomass burning or dust aerosols, AODs may remain unaffected or even increase during the lockdown period [36,37]. Beyond gaseous pollutants and AOD, there are some studies analyzing the changes in BC concentrations during the lockdown period [26,[38][39][40][41][42], which reported significant reductions (30-70%), but with large variability among regions.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on the AOD, a significant reduction (20-60%) was obtained in eastern China, while southeast Asia, eastern US and most European regions experienced a reduction reaching 40% [19,34,35]. However, in areas significantly impacted by seasonal biomass burning or dust aerosols, AODs may remain unaffected or even increase during the lockdown period [36,37]. Beyond gaseous pollutants and AOD, there are some studies analyzing the changes in BC concentrations during the lockdown period [26,[38][39][40][41][42], which reported significant reductions (30-70%), but with large variability among regions.…”
Section: Introductionmentioning
confidence: 99%
“…Kannur, India, reported decreased emissions (−62%), and a diurnal variation most pronounced during peak traffic hours was absent during the lockdown owing to the roads being deserted [70]. Figure 4 shows NO 2 emissions increased in the northern Colombian region due to events of long-range pollution transport, like regional biomass burning beginning at the end of March, during the lockdown, according to recent studies [33,34]; the air quality improvement shown in this period was partially annulled by the impact of these events.…”
Section: Discussionmentioning
confidence: 75%
“…The data show that mobility has dropped around the world as the spread of the virus has increased; public transportation systems were the most affected due to users refusing to use them in order to avoid social contact, and therefore the risk of contagion [32]. Other studies have shown an improvement in air quality in some Colombian cities due to mobility restrictions during the COVID-19 lockdown [33,34]. However, these studies did not look at the changes in atmospheric emissions associated with the observed air quality changes.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions of PM during the COVID-19 pandemic have been found in cities (Chauhan and Singh, 2020;Dumka et al, 2020;Singh et al, 2020) and industrial areas (Mandal and Pal, 2020;Ranjan et al, 2020;Selvam et al, 2020). Although traffic and PM emission activities have reduced, some studies report PM levels to increase (Arregocés et al, 2020;Broomandi et al, 2020). The increasing vehicle flow in urban and rural areas, industrial expansion, and dependence on the extraction of non-renewable resources expose Colombia to air pollution challenges (Casallas et al, 2020;Lopez-Restrepo et al, 2020).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results of their analysis reveal reductions of PM 2.5 and PM 10 by 40 and 44%, respectively. Arregocés et al (2020) considered variations in urban and industrial areas by limiting the data records of one monitoring station to be representative of a particular area. The authors found that there were reductions in PM2.5 of up to 86% in industrial zones during quarantine compared to days prior to quarantine.…”
Section: Accepted Manuscriptmentioning
confidence: 99%